Design of Android Based Smart Car - D. Wilfred Shiju (Institute of Advanced Engineering and Science, 2017)
Android smart car is designed with safety in mind. A simple and sensitiveline, included steering wheels and new voice events, this is designed to reduceinterruption so you can stay focused on the highway.This car which can be controlling using an Android APP for smart phones.A car is regularly an electronic mechanic machine that is guide by computer and electronic controlling programming. The innovation of the Smart Car technology to developing based on remote connection using android application can control the car movements. This system use Bluetooth device controller to control the mobile App. This Bluetooth device interface with UART communication. The UART receive the command via the Bluetooth device. This design is may helps to our rural citifies. This system is developing to help to self driving vehicles.